HASTE: A Platform for Rapid Post-Disaster Building Damage Assessment - Robinson, Caleb; Ortiz, Anthony; Fobi Nsutezo, Simone; Birge, Cameron; Machado, Meygha; Duarte, Marcelo; Rodriguez, Joaquin Rivero; Cintron Roman, Anthony; White, Kevin; Becker-Reshef, Inbal; Lavista Ferres, Juan M. (2026)
When a large disaster strikes, responders need a map of which buildings are damaged within hours, but the models that do well on public benchmarks assume matched before-and-after imagery and a training set drawn from similar past events, neither of which is usually available for a new disaster in its first day. We present HASTE (High-speed Assessment and Satellite Tracking for Emergencies), a no-code web platform that lets analysts who are not machine learning engineers produce per-building damage maps from post-disaster satellite imagery. HASTE implements two methods that share one interface. The first requires the user to label polygons over the post-disaster scene, trains a small semantic segmentation model on that single scene, runs it over the whole image, and joins the per-pixel output to existing building footprints. The second embeds every footprint with a pretrained vision model, requires the user to label a handful of buildings, and fits a logistic regression in the browser that scores the rest of the scene in seconds. We describe the platform, both methods, and the engineering that supports them. We also report preliminary experiments on xBD showing that foundation-model embeddings pooled over footprints separate damaged from intact buildings using post-disaster imagery alone, matching a fully supervised ResNet-50 baseline with a twentieth of its labels. HASTE and its predecessors have supported more than thirty real-world disaster responses since 2023, spanning earthquakes, hurricanes, cyclones, floods, wildfires, and tornadoes, delivering results to humanitarian partners within hours to days of imagery becoming available. We close with the directions we think are most promising, including vision-language assessment, active learning, and damage models for roads and other infrastructure. HASTE is open source at https://github.com/microsoft/haste.